The Production and Characterization of Carbon Composite from Coconut Shell Charcoal - Rampe, Meytij Jeanne; Setiaji, Bambang; Trisunaryanti, Wega; Triyono (International Coconut Community Journal, 2012)
Structure and chemical composition of coconut shell carbon with polyvinyl alcohol (PVA) as the stimulant through the observation of TG-DTA, SEM-EDS, FTIR and XRD had been studied. The process was carried out by calcining coconut shell charcoal at the temperature of 873 and 1023 K under nitrogen flow, then mixed with polyvinyl alcohol (PVA) under composition of 2.5 to 7.5% wt. in water solvent. The development of carbon composite structure was observed by heating the samples in Argon gas of 1673 K, the rate of temperature was 10 K/min in 3 hours. The products were then analyzed by TG-DTA, SEM-EDS, FTIR and XRD. The result showed that the products were in uniform particle size of micrometer dimensions and spherical particles in shape, with average content of C element at 97.44% wt., aromatic character and semi-crystalline structure.